Identifying traits and developing genetic sources for increased lodging resistance in elite high yielding wheat cultivars - Piñera Chavez, Francsico Javier (2016)
Lodging is a persistent phenomenon that reduces grain quality and grain yield of wheat. It is defined as the permanent displacement of the plant/shoots from their vertical position. During the Green revolution, wheat plant height was reduced to avoid lodging and allowed growers to increase nitrogen fertilization. This resulted in a considerable increase of grain yield. After the Green Revolution, plant growth regulators were used to further reduce plant height which continued increasing lodging resistance and grain yield. However, lodging susceptibility has not disappeared completely and as yields increase, there is evidence that growers cannot continue to rely on these strategies, raising the question of how to further improve lodging resistance of wheat. Collaborative studies by physiologists, biologists and engineers generated a deeper understanding of lodging (through stem and anchorage failure mechanisms) and the development of models of the lodging process, together with better crop husbandry or agronomic management strategies. Most of these studies were made on winter wheat under a reduced range of environmental conditions. This thesis attempted to further develop lodging mechanisms and models using spring wheat and a wider range of environmental and agronomic conditions and to investigate the genetic control of lodging-proof traits. Field experiments on spring wheat cultivars were carried out in irrigated conditions in NW Mexico and on a winter wheat Avalon x Cadenza doubled-haploid population in rainfed conditions in the UK. A lodging-proof crop was designed for spring wheat growing in NW Mexico that suggests the need for both increased structural stem biomass and a wider root plate spread (anchorage strength). The model also infers that trade-offs with grain yield will occur, mainly because of overlapping of the development of lodging traits with grain yield formation processes. Rapid selection tools for lodging resistance will play a primary role if lodging resistance is to be improved concurrently with grain yield. Fine mapping and validation of QTLs related to lodging traits identified in this study can be used to develop reliable genetic markers that can accelerate selection for lodging resistance concurrently with improvement of genetic yield potential.